P-56 Oacc virgins – challenges and opportunities of implementing outcome measures into clinical practice. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - McGregor, Becky; Hartley, Nigel
Abstract : Introduction: Health services are increasingly being required to demonstrate that they meet the needs of individual patients and their families, and that they do this in an effective and efficient way. This project describes the implementation of the 'Outcome Assessment and Complexity Collaborative' (OACC) suite of outcome measures into clinical practice within a hospice setting. Aims of the project: Implement using outcome measures in clinical practice Using OACC to assist with informing, allocation of workload and caseload management by evidencing the complexity of patients Understand, challenge and address some of the cultural barriers to implementing outcome measures in a hospice environment. Approach used: Results: The chart describes key learning points from implementing OACC into clinical practice. Conclusion: Effective implementation of OACC has required a stepped approach, an understanding of organisational readiness and key barriers. OACC is already proving an invaluable tool in articulating the complexity of patients within hospice services.